Turismo no espaço rural: um estudo multicaso nas regiões sul e sudoeste de Minas Gerais - Roque, Andreia Maria (2001)
This present work identifies the tourism activities course in the Minas Gerais' rural space, their typologies differences, their construction and development process, besides their interchange with the values and traditions of rural culture. Through the identification of the development of the rural space and the studyof urban population intentions in the moment they comebackto the country searching a warming feeling, this work found its answers. The problem approach was focused on quality and quantity research. The analyze of the results afifirmed that the tourism activities are inside the rural space reality in the south and southeast ofMinas Gerais. Besides that, it confirmed that there are differents terminologies for differents tourism realities such as rural tourism, tourism in the rural space, endogenous tourism, between others and also that these concepts don't necessarily refer to the same modality of activity. There are tourism activities in the rural space that don't interchange with the rural traditions or even with the regular agriculture activities, but the region analyzed presents a peculiar interrelation between the tourism and the custom agriculture productions. In general, the tourism activities find in the typical farm in the south and southeast of Minas Gerais a warming environment for their development.